Electronic and Ionic Conductivity of La0.95Sr0.05Ga0.95Mg0.05O3-δ (LSGM) Single Crystals. Issue 10 (1st January 2016) - Rupp, Ghislain M.; Glowacki, Michal; Fleig, Jürgen
Abstract : The defect chemistry and charge transport properties of La0.95 Sr0.05 Ga0.95 Mg0.05 O3-δ (LSGM) single crystals, grown by the Czochralski technique, were studied by impedance spectroscopy performed over a wide temperature range (180–800°C) and oxygen partial pressures from 0.21 to 1013 mbar. Owing to ion blocking Pt thin film electrodes impedance data showed a Warburg type 45° slope in the complex impedance plane. The spectra were analyzed by means of a generalized transmission line model which yielded the electronic and ionic conductivity, chemical and dielectric capacitance and the oxygen chemical diffusion coefficient. Activation energies for electronic (0.89 eV) and ionic charge transport (0.95 eV at low and 0.56 eV at high temperatures) were determined. Oxygen partial pressure dependent measurements revealed that the p-type conductivity is exactly proportional to pO2 1/4 and that the ionic transference number approaches 1 for low oxygen partial pressures and low temperatures. Additional Hebb-Wagner type DC polarization experiments were carried out to determine the n- and p-type conductivities in a broad chemical potential range and to verify the results obtained by the AC impedance measurements.